Pemetaan UMKM Desa Ngabul dan Penguatan Strategi Pemasaran Digital Berbasis Lokasi - Eka Yuliyanti; Azis Nur Rosyid; Zati Rizka Fadhila; Rahmania Mustahidda; Andi Kartika (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
This community service program aims to strengthen MSMEs in Ngabul Village through comprehensive business mapping and location-based digital marketing assistance. The mapping process was carried out through direct field observations involving several business actors, documenting product types, production capacity, marketing channels, and the challenges they encounter in expanding market reach. Findings indicate that most MSMEs hold significant potential, supported by the presence of local tourist destinations such as Ngetuk Garden and the Jepara Durian Market, which consistently attract visitors. However, the adoption of digital media remains limited, particularly in content management, the use of location-based features, and the selection of appropriate platforms for each product category. To address these gaps, the community service team provided practical training focused on basic content creation techniques, location-based promotional strategies, and maintaining consistent uploads to enhance visibility among potential customers. Through a tailored and hands-on approach, this program is expected to improve MSMEs’ capacity to adapt to technological advancements and expand their marketing opportunities, thereby contributing to the economic development of Ngabul Village.